An epistemic justice account of students' experiences of feedback - Vilakazi, Bella Phetheni (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning)
I am a storyteller. I believe in the power of stories to share experiences and to elucidate thoughts and ideas and to help us to make sense of complex social practices. This thesis includes the stories of five young women who were learning to become teachers. As they shared their stories with me, I share them with you. This study includes their stories of receiving feedback. These stories are structured within the Narrative Inquiry dimensions of temporality, place and context. These dimensions suggest that stories are historical and move through time, stories are shaped by place and the context in which they unfold (Clandinin, 2013). Furthermore, these stories demonstrate how feedback can serve to give access to powerful knowledge and can serve to recognise who our students are and what they bring to the academy (Hordern, 2018). But feedback can also serve to misrecognise. Much has been written and reported about the barriers preventing students from acting on the feedback on their assignment tasks in higher education. In this study, I argue that feedback is a pedagogic practice that can support students to gain epistemic access. Feedback can only achieve this if it makes the expectations explicit for students to make sense of and make meaning for themselves and if it is offered in a dialogical format which recognises the students, their attempts, their identities, and their knowledge. The research question of this study, 'How do experiences of forms of feedback affect female undergraduate student teachers' chances of epistemic access?', is not unusual. There have been many research projects that have been carried out that examine students' experiences of feedback (for example, Evans, 2013; Basey, Maines, & Francis, 2014; Nicol et al.; 2014; Carless, 2019; Winstone et al., 2021). But I identified a gap where feedback has not, to my knowledge, been studied directly through the lenses of Epistemic Justice towards Parity of Participation. This study interpreted five undergraduate student teachers' feedback experiences through these lenses. Narrative inquiry enabled me to design this study in ways that foregrounded experience. Data was collected through multiple conversations during which I organised the participants' life stories of feedback within the dimensions of temporality, place and context, and sociality. Miranda Fricker's (2007) theory of Epistemic Justice and Fraser's norm of Parity of Participation (2000) framed this study. I engaged with Fricker and Fraser's literature meaningfully as a reader and researcher. I established an understanding of how the lenses offered by Fraser and Fricker allowed me to make sense of the literature more generally, in social life and on the pedagogic practice of feedback. Fricker's theory of Epistemic Justice considers the epistemically unjust, gendered, raced and classed, experiences of epistemic agents. Fricker (2007) draws on two central concepts to account for epistemic injustices: Testimonial Injustice and Hermeneutical Injustice. Fricker (2007; 2003) explains that testimonial injustice occurs within a testimonial exchange setting, when an epistemic agent as a speaker gives testimony of the epistemic agent's experiences and knowledge but is not awarded the credibility the speaker deserves (Fricker, 2003). Epistemic agents who participate in a testimonial exchange need to overcome bias and prejudice in order to evaluate testimonies with the degree of fairness the testimony deserves (Fricker, 2013; 2016). Hermeneutical injustice occurs when an epistemic agent is unable to make sense and make meaning of their social experiences. Hermeneutical injustice strengthens when the epistemic agent is prevented from gaining access to resources that might help with sense making and meaning making of these social experiences (Dielman, 2012; Fricker, 2016). To ensure that meaning can be made between people and groups of people, there needs to be some shared understandings of the purpose and process of sense making and meaning-making "“ or a willingness to co-create such shared understandings. Fraser's norm of Participatory Parity enabled a consideration of the larger world of political and economic systems that give rise to social injustice. In this study, the theories of Fricker and Fraser are used to illuminate experiences of feedback of the five undergraduate student teachers who are the participants in this study and how these translate to epistemic and social injustice. The norm of Participatory Parity is considered where feedback allowed or restricted participants from participating on an equal footing in the feedback process. Narrative inquiry, a research methodology that is used to study experiences, was used to inform research strategies of this study. Participants' experiences, data collection and organising the narratives demonstrated the dimensions of temporality and space. The thesis includes biographical vignettes for each of the participants in the study, interspersed with data from across all five participants. The key findings of this study show that feedback generally operates at the surface levels of grammar correction. In light of the theoretical lenses of this study, I argue that the feedback experiences they shared generally did not recognise their attempts and the identities and knowledges they brought to the tasks. Because the focus was on superficial correction of the specific task, the feedback failed to create conditions for the (re)distribution of knowledge. At times the feedback exerted power on participants. Because the feedback was generally in the form of one directional correction (with little space for interaction with the feedback or dialogue with the assessor), this caused status subordination of participants in the epistemic spaces of teaching practice. Lastly, the lack of clarity of feedback was harmful to the potential for dialogical feedback. Such feedback caused participants to experience forms of epistemic injustice in the form of hermeneutical injustice where it failed to create conditions for the distribution of knowledge. Feedback also caused participants to experience testimonial injustice where it failed to create conditions for recognising participants' processes of sense-making and meaning-making in the various assignment tasks. Participatory Parity could not occur because the processes of recognition and redistribution were constrained. Feedback then created fertile conditions of epistemic injustice to occur, and participants were likely to have failed to gain the much needed epistemic access. This study is not the story of bad, uncaring academics; the study acknowledges the context of large classes and heavy workloads in which feedback is or is not given. Rather, this is the story of five women trying to make their way through the university and out into the world as teachers. The study calls for better theorising of feedback and more support for both academics and students to develop feedback literacy so that feedback might serve as a dialogical pedagogic practice that enables epistemic justice.
Keywords: Feedback (Psychology); Experience; Narrative inquiry (Research method); Critical thinking; Caring -- Moral and ethical aspects; Epistemic access